ANEMONA: A language for programming NEtwork MONitoring applications - Fernandes H.D.H.* (2003)
We present ANEMONA: a language for distributed network management programming. The compilation of an ANEMONA program generates code for configuring DisMan MIB's thus automating a complex task that is prone to errors if done manually. The language allows the definition of expressions of managed objects that are monitored, as well as triggers that when fired may indicate the occurrence of associated events, which are also defined by the language. A translator for the language was implemented that generates code for configuring the Expression MIB and the Event MIB. Experimental results are presented, including an ANEMONA program that detects TCP Syn Flooding attacks, and a program for detecting steep variations on the utilization of monitored links.